Bulky bis(imidazole) and 2‐sulfoterephthalate Assisted 3‐D Cu(II) and 2‐D Mn(II) Coordination Polymers: Topology, Diversity in Metal Containing Nodes and Spectral Elucidation. Issue 19 (29th November 2016) - Das, Kuheli; Datta, Amitabha; Mane, Sandeep B.; Mendiratta, Shruti; Massera, Chiara; Garribba, Eugenio; Huang, Jui‐Hsien; Hung, Chen‐Hsiung; Akitsu, Takashiro
Abstract: This work presents the synthesis of a 3‐D Cu(II) framework represented by a 4, 6‐c 2‐nodal net of the type fsc employing the bifunctional template group sulfonate‐carboxylate and the dia precursor (dia=9, 10‐di(1H‐imidazol‐1‐yl)anthracene). The high versatility of the N‐donor and carboxylate ligands also yields a 2‐D Mn chain described by a pcu primitive cubic net. The solvent‐dependent EPR studies for both the CPs are also illustrated. Variable temperature magnetic susceptibility confirms that both ferromagnetic and antiferromanetic interactions coexist in 1 among the different geometrical arrangement of Cu(II) ions. Abstract : The Cu(II) and Mn(II) CPs are generated where the first one represents as a 3‐D framework by a 4, 6‐c 2‐nodal net of the type fsc and the later shows a 2‐D chain by a pcu primitive cubic net. This contribution divulges the consequence of the metal ion effect from a topological point of view. Both the CPs are characterized by emission and solvent dependent EPR spectroscopy.